2019
DOI: 10.1039/c9ee02058f
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability of existing and planned coal-fired power plants in Developing Asia to changes in climate and water resources

Abstract: Water constraints on the coal-fired power plants and deployment of CO2 capture technology in Developing Asia at multiple scales.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 72 publications
(80 reference statements)
2
23
0
Order By: Relevance
“…One study of Great Britain found that with an approximate halving of reliable thermal capacity on freshwater under climate change, results in an additional £18-19 billion in system costs over 40 years due to more costly cooling, location options, more fuel use and different capacity decisions 11 . Concerns about climate change have motivated several high-impact studies focusing on the impact of reduced cooling water availability and increased cooling water temperatures on power plant reliability and energy production [12][13][14][15][16] . One notable study at the European scale estimated electricity price impacts from drought under climate change on hydro and thermal plant, finding negative impacts in southern and southeastern European countries, but producer benefits in northern hydro producing countries, which can sell electricity at higher prices to compensate for power plant outages in the south 17 .…”
mentioning
confidence: 99%
“…One study of Great Britain found that with an approximate halving of reliable thermal capacity on freshwater under climate change, results in an additional £18-19 billion in system costs over 40 years due to more costly cooling, location options, more fuel use and different capacity decisions 11 . Concerns about climate change have motivated several high-impact studies focusing on the impact of reduced cooling water availability and increased cooling water temperatures on power plant reliability and energy production [12][13][14][15][16] . One notable study at the European scale estimated electricity price impacts from drought under climate change on hydro and thermal plant, finding negative impacts in southern and southeastern European countries, but producer benefits in northern hydro producing countries, which can sell electricity at higher prices to compensate for power plant outages in the south 17 .…”
mentioning
confidence: 99%
“…While our study focuses on Texas, this will likely affect all US power systems as their thermal generator fleets and loads experience warming. An important mediating factor in how climate change will affect future thermal fleets is how those fleets evolve over time (Wang et al 2019). We found that shifting to robust cooling technologies nearly eliminates thermal deratings in high demand hours (SI.3.2), indicating adaptation potential within the existing generator fleet (van Vliet et al 2016).…”
Section: Discussionmentioning
confidence: 86%
“…Several studies indicate the importance of resource redistribution in alleviating localized resource constraints, including via trade [68,93,102] and electricity transmission [164][165][166], and water conveyance [62]. Thus, infrastructure that allows for the movement of commodities and resources from resource-rich to resource-poor locations stands out as one of the most important nexus solutions.…”
Section: Resource Redistributionmentioning
confidence: 99%